2016
DOI: 10.5586/aa.1666
|View full text |Cite
|
Sign up to set email alerts
|

Composition and structure of the flora in intra-urban railway areas

Abstract: Railway areas are considered as large greenspaces and are recognized important in improving the biodiversity and dynamic of urban flora. In this study, we examined the flora composition and diversity along intra-city railway lines in Lublin, SE Poland and Lviv, W Ukraine. The flora has been analyzed in terms of species composition (multivariate ordination techniques), life span, life form, type of pollination mode, seed dispersal, life strategy sensu Grime, hemerophoby, urbanity degree, and in terms of habitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
2
16
0
1
Order By: Relevance
“…In this study, we build on earlier work and report an analysis of the flora of intraurban railway areas located in the cities of Lublin and Lviv [29][30][31]. In particular, we compared the richness and abundance of the invasive alien plants recorded within railway areas.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we build on earlier work and report an analysis of the flora of intraurban railway areas located in the cities of Lublin and Lviv [29][30][31]. In particular, we compared the richness and abundance of the invasive alien plants recorded within railway areas.…”
Section: Introductionmentioning
confidence: 99%
“…Залізничне сполучення сприяє також активним міграціям адвентивних видів рослин, у тому числі й інвазійних видів. Окрім того, залізничні насипи є техногенними екотопами (забруднені нафтопродуктами, важкими металами, продуктами видування й опадання сипучих вантажів: вугілля, руди, цементу тощо), і саме на них формується своєрідний рослинний комплекс [26,[29][30][31].…”
unclassified
“…However, in general, our study showed that the character of the flora associated with railway areas is mostly influenced by the degree of anthropogenic pressure, the environmental conditions prevailing in such areas and probably the land use along railways. All these factors, including railway management practices, interacted and evidently impacted on the richness and composition of the flora (Wrzesień et al, 2016). Our analysis will contribute to the establishment of a broader understanding of the management and conservation potential of this land use type.…”
Section: Discussionmentioning
confidence: 89%